Complicaciones en pacientes con infección por COVID 19 severo en unidad de cuidados intensivo en un centro de cuarto nivel en Bogotá, Colombia - Andy Dieter Schreiber (Infectio)
Objective: To analyze the complications experienced by patients admitted to the ICU with severe COVID-19 at a fourth-level hospital in Bogotá, Colombia.Materials and Methods: This retrospective, descriptive, cross-sectional study included 181 patients aged over 18 years with severe COVID-19 admitted to the ICU at Fundación Cardioinfantil from August 2020 to May 2021. Results: Infections were the most prevalent complication, occurring in 72.9% of patients, with pulmonary superinfections and tracheitis being the most common. Neuropathy was observed in 18.7% of patients. Swallowing disorders were noted in 74% of patients, with 52.5% continuing to experience swallowing difficulties at discharge, leading to gastrostomy in 4.9%. Acute kidney injury was present in 26.5% of patients; 7.1% required de novo renal replacement therapy, and 2.8% needed renal replacement therapy at discharge. Myocardial injury was documented in 13.8% of patients. Discussion: The study highlights the extensive range of complications affecting post-COVID-19 patients, particularly those with severe infections. Polyneuropathy and myopathy are reported in 25-45% of critically ill patients, whereas our study documented neuropathy in 18.7%. Swallowing disorders, occurring in 74% of pa-tients, led to a gastrostomy rate of 4.9%, slightly above the literature range of 1.9%-4.8%. Tracheostomy, used as an alternative to reduce sedation and mechanical ventilation time, was performed in 21.5% of patients, resulting in reduced ICU and ward stays. Conclusions: The most frequent ICU complications were healthcare-associated infections, underscoring the importance of early detection and preventive strategies. Neuromuscular sequelae, such as neuropathy, are significant factors affecting patient outcomes, highlighting the need for targeted rehabilitation methods.